Effect of Si Addition on Microstructure and Mechanical Properties of Dual Two-Phase Intermetallic Alloys Based on the Ni3Al-Ni3V Pseudo-Binary Alloy System. Issue 1760 (2nd February 2015) - Hamada, Yuki; Kaneno, Yasuyuki; Numakura, Hiroshi; Takasugi, Takayuki
ABSTRACT: The effect of Si addition on microstructure and mechanical properties of dual two-phase intermetallic alloys was investigated. Si was added to the base alloy composition Ni75 Al9 V13 Nb3 + 50 wt. ppm B by three substitution ways in which Si was substituted either for Ni, for Al and for V, respectively. The alloys added with 1 at.% Si showed a dual two-phase microstructure composed of Ni3 Al (L12 ) and Ni3 V (D022 ) phases, while the alloys added with over 2 at.% Si exhibited the same dual two-phase microstructure but contained third phases. The third phases were G phase (Ni16 Si7 Nb6 ) and A2 phase (the bcc solid solution consisting of Nb and V). Yield and tensile strength of the 1 at.% Si-added alloys were high in the alloy in which Si was substituted for Al but low in the alloys in which Si was substituted for Ni or for V, in comparison with those of the base alloy. Tensile elongation was lower than that of the base alloy irrespective of substitution ways. The density of the Si added alloys was close to or slightly lower than that of the base alloy. Oxidation resistance of the Si added alloy was increased. Si addition to the dual two-phase intermetallic alloys is beneficial for reducing the density and enhancing the oxidation resistance without a harmful reduction of strength properties.